Development of Class X Mathematics Learning Media Powtoon on The Merdeka Curriculum - Gaby Maharani Gurning; Riza Agustiani; Dyah Rahmawati (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Kurikulum Pengembangan Pengajaran dan Pembelajaran (Center of Curriculum Studies, Teaching and Learning Development), 2025)
This research was conducted with the aim of producing innovative powtoon-based learning media to help implement the Merdeka Curriculum in Mathematics Lessons on SPLTV material which has a valid and practical category and has a potential effect, especially on students' mathematical problem solving skills. This research was conducted using the Research and Development (R&D) research procedure using the ADDIE model which has five stages, namely analysis, design, development, implementation, evaluation. The data collection techniques used are questionnaires, test questions and interviews. The research subjects were grade X students at MAN 2 Palembang. The results of this study indicate that the powtoon animation video developed has a valid category with a score of 3.9 from the Media Expert and 4.6 from the Material Expert. Meanwhile, the practicality questionnaire shows a score of 4.2 for the One-to-One trial which contains 3 students with different abilities, then 4.06 for the Small Group test which consists of 3 groups where each group contains 3 members who work together in solving problems, and finally 4.2 for the Field Test which consists of 1 class X.6 which contains 30 students. . While the potential effect on this powtoon animation video can be seen from the learning outcomes of students who show learning outcomes with an average of 81 which states that learning media provides a potential effect on very good learning outcomes. In addition, not only does it provide a potential effect on learning outcomes but new findings that learning animation videos are also able to increase student motivation and interest in exploring SPLTV material.